Kualitas Perairan Pantai Medewi Di Kabupaten Jembrana Yang Dimanfaatkan Sebagai Aktivitas Pariwisata - Ni Luh Putu Mahendra Dewi (Program Studi Teknik Lingkungan Unmas Denpasar, 2021)
Medewi Beach is one of the beaches in Jembrana Regency. Medewi beach is being developed marine tourism spots, but its have more problem with the increasing tourism activity and followed by activities of residents and settlements that disturb the environment, especially an increasing domestic waste to the coastal. So it’s has an impact decreasing the waters quality. This paper reports the examination to determine Medewi beach water quality for physics, chemical and biology parameters. Water sampling was taken during the rainy season and dry season. The results of the water sample measurements were compared to the environmental quality standards and standard criteria of environmental damage by Bali Governor Regulation No. 16 in 2016 and water quality classification by the Storet Method which refers to KEPMENLH No.115 of 2003. The results showed of some parameters whose values exceeded the standart. Those parameters were in the rainy season were Pb, Nitrate, Coliform and E coli and the dry season were Pb and Coliform that exceeded the standard. The STORET assessment results of Medewi beach has a total score of -42 which is classified as heavily polluted and that’s less suitable for marine tourism.